Modifying spectral conjugate gradient method for solving Iteration Problems (Statistics, Optimization & Information Computing, 2026)
One diffuse and simple technique for minimizing the models is to use spectral conjugate gradients. In this work, we construct a unique Spectrum using the gradient approach to expansion a novel search Path, we have proven that the novel spectral approach Possesses the descent property and that the spectrum methodology is globally convergent. The experimental results indicate that for the test problems, the suggested methodology may be computed in conjunction with alternative conjugate gradient techniques.